JENIS-JENIS SEMUT (HYMENOPTERA: FORMICIDAE) PADA PERKEBUNAN KELAPA SAWIT DI SEKITAR KAMPUS UNIVERSITAS PASIR PENGARAIAN - Sari, Riska Winda; Yolanda, Rofiza; Purnama, Arief Anthonius (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The aims of this study was to determine the genera of ants on palm oil plantations around Pasir Pengaraian University. This study was conducted from October to December 2014 by using survey method with random sampling technique. The sample was collected by pit fall trap and bait trap. The samples were collected with a 2 x 2 meter square plots on palm oil tree at campus gate, around campus and behind the campus. Results showed the ants with 4 subfamily and 10 genera. They were Dolicoderus, Anoplolepis, Camponotus, Oecopylla, Paratrechina, Polyrhachis Lophomyrmex, Solenopsis, Odontomachus dan Odontoponera